TEAM-BASED ELECTRONIC PORTFOLIO IN THE TEACHING & LEARNING OF ORDINARY DIFFERENTIAL EQUATIONS - Zainal Abidin, Azizan (2010)
Obtaining evidence of student learning is a vital aspect in acquiring accreditation of programs in institutions of higher learning. With the limitations of the traditional assessment approach of pen and paper as a measuring tool, educators seek for alternative assessment methods that are able to measure other than technical skills. E-portfolio is an example of such an alternative. However, with a large class size of over two hundred students, implementation could be an obstacle. The instructor (cum the first author) thus implements team-based e-portfolio that requires students to work collaboratively. The objective of the team-based learning e-portfolio assessment is to develop an e-portfolio that consists of biographical details, solutions to application problems in first order ordinary differential equations, students’ reflections of learning experience and evaluation of the course and delivery from students’ perspective. The implementation of the e-portfolio assessment is to measure participants’ process skills, i.e. in terms of communicating, organizing, classifying, constructing and designing using multi-media skills, analyzing, evaluating the course and their instructor education delivery and reflecting on their learning endeavor in building the e-portfolio as an integral part of their learning assessment. How do participants rate such an assessment approach? The objective of this research is to discover participants’ feedback and rating towards the e-portfolio assessment in the teaching and learning of the Differential Equations course. This paper intends to discuss the outcomes of the implementation of team-based e-portfolio assessment from the learners’ point of view. The study employs a single group ex-post facto quantitative and qualitative research. Two hundred and forty two first semester engineering students of Universiti Tekologi PETRONAS (UTP) are involved in the study. These students are in the Petroleum Geosciences, Petroleum and Mechanical Engineering discipline enrolled for the July 2009 semester. All participants have at least passed the pre-requisite of passing a four-credit-hour Calculus course at UTP, or an equivalent course obtained from other institutions of higher learning. After five weeks of lectures on first order ordinary differential equations, the instructor posts structured instructions pertaining to the development of the e-portfolio using the university electronic learning support system; moodle. The online information includes a definition of the e-portfolio, the objectives of the e-portfolio development, and complete instructions with the provision of an e-portfolio template as a guide for participants. Using random sampling, the participants form groups of five. Participants team up and select five questions from a pool of twenty problems. The researcher gives a short demonstration of Power Point with animation and Microsoft Equation Editor Version 3.0 that participants will need in order to develop the e-portfolio. Most of the participants are quite familiar with Power Point but not the animation tools and almost all never knew about the existence of the Equation Editor. For this paper discussion is focused on data collected at the end of July 2009 semester from a questionnaire, participants’ ratings and their reflections of their learning experiences. The deliverables reflect participants’ process skills and the feedback provide useful information to the instructor and evidence of student learning for accreditation purposes.